Outcome of Percutaneous Nephrolithotomy Without JJ Stent in Comparison to Percutaneous Nephrolithotomy With JJ Stent (Bangladesh Journal of Urology, 2020)
Objective: This study aims to evaluate the outcomes of PCNL without JJ ureteric stent in comparison to PCNL with JJ ureteric stent.Patients and Methods: This observational study intended to compare the outcome between PCNL without JJ stent and PCNL with JJ stent of 50 cases of renal stone disease according to the inclusion and exclusion criteria and randomly assigned to Group - A (PCNL without JJ stent) and Group - B (PCNL with JJ stent). This study was conducted in the department of urology, Dhaka Medical College Hospital from July 2014 to June 2016. During postoperative period, both groups were compared with respect to fever, loin pain, dysuria, frequency of micturation, duration of haematuria, continuation of urine leakage, hospital stay, urinoma and hematoma and urinary tract infection.Results: Among the 50 patients, the mean postoperative hospital stay was significantly longer in PCNL with JJ stent (4.48 ± 2.14 days) than that of PCNL without JJ stent (2.60 ± 0.50 days). The continuation of urine leakage at the site of percutaneous tract was also significantly longer in PCNL with JJ stent than in PCNL without JJ stent (10.8 ± 3.18 hours vs 14.14 ± 3.28 hours, P